Diagnostic value and safety of medical thoracoscopy in tuberculous pleural effusion. Issue 9 (September 2015) - Wang, Zhen; Xu, Li-Li; Wu, Yan-Bing; Wang, Xiao-Juan; Yang, Yuan; Zhang, Jun; Tong, Zhao-Hui; Shi, Huan-Zhong
Abstract Background Differentiating tuberculous pleural effusion from other lymphocytic pleural effusions is often challenging. This retrospective study aimed to assess the efficacy and safety of medical thoracoscopy in patients with suspected tuberculous pleural effusion. Methods Between July 2005 and June 2014, patients with pleural effusions of unknown etiologies underwent medical thoracoscopy in our institute after less invasive means of diagnosis had failed. Demographic, radiographic, procedural, and histological data of patients with tuberculous pleural effusion were analyzed. Results During this 9-year study, 333 of 833 patients with pleural effusion were confirmed to have tuberculous pleurisy. Under thoracoscopy, we observed pleural nodules in 69.4%, pleural adhesion in 66.7%, hyperemia in 60.7%, plaque-like lesions in 6.0%, ulceration in 1.5% of patients with tuberculous pleurisy. Pleural biopsy revealed the presence of Mycobacterium tuberculosis in the pleural tissue or/and demonstration of caseating granulomas in 330 (99.1%) patients. No serious adverse events were recorded, and the most common minor complication was transient chest pain (43.2%) from the indwelling chest tube. Conclusions Our data showed that medical thoracoscopy is a simple procedure with high diagnostic yield and excellent safety for the diagnosis of tuberculous pleural effusion.